Cosmogonia profana: uma leitura de O visitante, de Osman Lins - Soares Filho, Antonio Coutinho (2017)
In the whole of Brazilian literature, Osman Lins is a name that stands out for the quality and diversity of his production. Novelist, playwright, essayist, among other attributions, the writer has an aesthetic refinement as well as a reflexive posture in face of the cultural, social and political obstacles of the country. The osmanianos studies often highlight the author's romanesque experiments in his so-called maturity phase. Not exclusively, the prior creation to this period still lacks major critical exams, such as the novel debut, The Visitor (1955) corpus of this research. Besides the interesting textual warp, this work presents a humble fortune review, which gives rise to this work. It should be added that on several occasions the writer affirms that the cosmogonical attitude along with the preoccupations with the national ills and the reflection on the creative process, guide his life and the literary work. That said, one wonders how this worldview is presented in The Visitor. Taking into account the traced interdiscurssive of the narrative and the novelist’s social-critcism and point of view. The proposed analysis considers the mythological, biblical, and liturgical inscriptions as well as the development of his story in the plot. In the face of it, there’s a hypothesis is that Lins, in a subversive modulation brings to the scene elements of the Eden myth and Christian liturgy but he also highlights the contradictions of a society that privileges appearances, victimizing the woman mainly. In the theoretical-critical articulation a review of the analytical itinerary of the corpus is done, with the help of Nitrini (1987, 2001, 2003, 2004), Andrade (2001, 2004, 2014) and Ribeiro (2016), among others. The concepts of threshold — Benjamin (1987), Gagnebin (2010); Devices and profanation, according to Agamben (2009, 2010, respectively), also guide this research. The theoretical-critical complete this framework itself, brings reflections on the poetic–myth creation according to the thinking of Mielietinski (1987), Eliade (2010), Perrone-Moisés (1998), Benjamin (2013), Derrida (2005) and Bastazin (2006). The methodological course, starting from the narrative structure and the critical fortune of the work, examines the aesthetic inversions operationalized by osmanian writing. The visitor, Osman Lins' first creative gesture despite his myth-poetic features presents through an introspective plot a sharp vision of the manipulation game that sustains the society, a principle that distorts the essence of the being and search to conceal the contradictory nature of power